Purifikasi Imunoglobulin Yolk Pada Ayam yang Divaksin terhadap Ekskretori/Sekretori Stadium L3 Ascaridia galli - Darmawi Darmawi; Ummu Balqis; Risa Tiuria; Muhammad Hambal; Samadi Samadi (Agricultural Faculty, 2010)
Purification yolk immunoglobulin of hens vaccinated against excretory/secretory Ascaridia galli L3 larvae stageABSTRACT. The main immunoglobulin fraction of poultry is called IgY, in order to distinguish it from the mammalian IgG. This article focus on purification yolk immunoglobulin of hens vaccinated against excretory/secretory Ascaridia galli larvae to obtained purity IgY. Active vaccinations with excretory/secretory antigen were applied intra muscularly of chickens with an initial dose of 80 g. The vaccinations were repeated three times with dose of each 60 g with an interval of one week. The first vaccinations were excretory/secretory antigen mixed with Fruend Adjuvant Complete and subsequently mixed with Freund Adjuvant Incomplete. Antibody response in yolk was detected at weekly intervals by agar gel precipitation test (AGPT). The chickens eggs were collected from 49 day after vaccinations. IgY was extracted from egg yolks by means of ammonium sulphate and purified using fast performance liquid chromatography (FPLC). The purity of anti-ekscretory/secretory IgY protein was determined by Bradford method ( = 280 nm). The result showed that antibody in yolk was begun detect with AGPT at four weeks after vaccination. IgY concentration after purification was 0,875 0.251 mg/ml. This study has shown that the product released in vitro by L3 stage A. galli is capable of stimulating humoral immunity by mean of producing antibody through yolk as biologic manufacturer could be a good choice.